Content and composition of essential oil in lemon balm (Lippia alba (Mill) N.E.Br.) grown with ammonium and nitrate in light environments - Lima, Janderson Do Carmo; Santos, Anacleto Ranulfo Dos; Soua, Aline Dos Anjos; Santos, Marcelo Batista Dos; Alves, Pericles Barreto (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
Medicinal plants have great potential for the production of phytocompounds, which are used for various purposes, mainly in drugs and cosmetics. The aim of this study was to evaluate the essential oil from Lippia alba cultivated with ammonium (NH4+) and nitrate (NO3-) under light environments. The plants were subjected to five ratios of NH4+: NO3- with nutritious solutions and four light environments (red, aluminet and black mesh, and full sun). The experiment design was entirely randomized with a 5 × 4 interaction and five repetitions per treatment, totaling 100 experiment units. The seedlings were transplanted to 6 dm3 plastic pots containing a mixture of washed sand + vermiculite at a ratio of 2:1. At 120 days after application of the treatments, the following parameters were evaluated: yield, content and composition of essential oil. The extraction was performed with the hydrodistillation method using drag of steam for a period of 2 hours. Nine compounds were found in the essential oil,  of which  neral and geranial represented 90% of the blend. Carvone was only found in the treatment with plants grown under the red mesh and with the 50:50 ratio of ammonium and nitrate.